Pengaruh Kepemimpinan Transaksional dan Kepemimpinan Transformasional Terhadap Kepuasan Kerja dan Kinerja Dosen Universitas Tanjungpura Pontianak - Rosnani, Titik (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2012)
The central theme of this research is that the job satisfaction and the lecturers"™ performance are increasing because of the roles of transactional and the transformational leadership. The purpose of this research is to examine and analyze the influence of these two leadership styles in University of Tanjungpura with main focus on the study of Human Resources Management. This research employs survey design   in the form of verification   research. The sampling design used in this research is stratified random. From 987 lecturers in University of Tanjungpura, 60 respondents (lecturers) are drawn as samples from nine faculties and participate in this research. The data are obtained from the collected questionnaires and they are analyzed by using path analysis. The results have shown that (1) the transactional leadership has a insignificantly positive influence on the lecturer"™s job satisfaction, (2) the transactional leadership has a insignificantly positive influence on the lecturer"™s work performance, (3) the transformational leadership has a significantly positive influence on   the lecturer"™s job satisfaction, (4) the transformational leadership has a significantly influence on the   lecturer"™s work performance, and (5)   the job satisfaction has a significantly positive influence on the lecturer"™s work performance.